Nilai VFA dan NH3 Rumput Alam Padang Penggembalaan Kecamatan Haharu Kabupaten Sumba Timur - Marselinus Hambakodu; Elvis Pati Ranja; Made Adi Sudarma (Jurnal Ilmu Peternakan Terapan, 2021)
This study aims to determine the value of volatile fatty acids (VFA) and ammonia (NH3) of natural grass in grazing fields in vitro. The study used a direct survey method in the field. Natural grass was tested in vitro using Bali cattle rumen fluid. The data obtained were analyzed using descriptive analysis based on the mean and standard deviation. Natural grass consisted of Heteropogon insignis, Bracharia decumbens, Bothriochloa ischaemum. The measurement of the value of VFA uses steam distillation, while the method of measuring the value of NH3 uses Conway micro diffusion. The results showed that Bracharia decumbens grass had a total VFA value of 74.48 mM and an NH3 value of 8.50 mM which was higher than Heteropogon insignis grass (total VFA 65.79 mM and NH3 6.67 mM), and Bothriochloa ischaemum grass (total VFA 60.64 mM and NH3 5.34 mM). The conclusion of this study was based on the value of VFA and NH3, Bracharia decumbens grass was a natural grass that may be cultivated for ruminants.